Life Cycle Assessment of Upgrade Options of a Municipal Sewage Treatment Plant for Energy Self-sufficient. Issue 1 (June 2020) - Sun, Xuefei; Jin, Mingji; Li, Na; Piao, Wenhua
Abstract: The environmental impact of four municipal sewage treatment scenarios were investigated by life cycle assessment (LCA). The environmental impacts were assessed with four categories: acidification potential (AP), eutrophication potential (EP), global warming potential (GWP), and human toxicity potential (HTP). Compared to the current operation scheme (Scenario 1), EP was significantly reduced but AP, GWP and HTP was increased in A2O-MBRprocess (Scenario 2). Compared to the Scenario 2, Scenario 3 (water source heat pump) and Scenario 4 (sludge anaerobic digestion) processes for the energy self-sufficient alternatives achieved the greatest environmental improvement in all impact categories. These results suggested that the proposed energy self-sufficient scenarios may greatly reduce the environmental impact of energy consumption in the whole sewage treatment process.